2007
DOI: 10.1128/iai.01499-06
|View full text |Cite
|
Sign up to set email alerts
|

The pyrH Gene of Vibrio vulnificus Is an Essential In Vivo Survival Factor

Abstract: We have suggested an important role of the pyrH gene during the infectious process of Vibrio vulnificus. Previously, we have identified 12 genes expressed preferentially during human infections by using in vivoinduced antigen technology. Among the in vivo-expressed genes, pyrH encodes UMP kinase catalyzing UMP phosphorylation. Introduction of a deletion mutation to the pyrH gene was lethal to V. vulnificus, and an insertional mutant showed a high frequency of curing. We constructed a site-directed mutant strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Previous studies have shown that some ivi genes are related to bacterial pathogenesis (Deb et al 2002;Kim et al 2003;Fernández et al 2004;Akhtar et al 2006;Lee et al 2007). To confirm these findings, three ivi genes identified in this study were evaluated for their roles in virulence of V. anguillarum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that some ivi genes are related to bacterial pathogenesis (Deb et al 2002;Kim et al 2003;Fernández et al 2004;Akhtar et al 2006;Lee et al 2007). To confirm these findings, three ivi genes identified in this study were evaluated for their roles in virulence of V. anguillarum.…”
Section: Discussionmentioning
confidence: 99%
“…Among these technologies, IVIAT is significantly superior to other reported in vivo expression technologies because it avoids the use of animal model (Handfield et al 2005). It has been applied in several important pathogenic bacteria for the identification of new virulent factors (Deb et al 2002;Kim et al 2003;Fernández et al 2004;Akhtar et al 2006;Lee et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For iron overload experiments in mice, 8-week-old female CD1 mice were pretreated i.p. with 450 g of ferric ammonium citrate (approximately 80 g of elemental iron) (Sigma-Aldrich) 50 min before the bacterial infection (25).…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial translocation from the upper chamber to the lower chamber was measured by twofold serial dilution and subsequent bacterial viable cell counting on 2.5% NaCl HI agar plates as previously described (20).…”
Section: Epithelial Translocation (Invasion) Of the V Vulnificus In mentioning
confidence: 99%
“…Logarithmicphase V. vulnificus strains were inoculated in 75% NPS in PBS at an initial concentration of 1 × 10 8 CFU/ml and incubated at 37℃. Viable V. vulnificus cells were counted on 2.5% NaCl HI agar plates after 30 and 60 min of incubation as previously described (20,21). …”
Section: Serum Bactericidal Activitymentioning
confidence: 99%